Anatomical Asplenia in Cat Eye Syndrome: An Expansion of the Disease Spectrum. (16th April 2013) - Chellapandian, DeepakBabu; Schneider, Adele
Abstract : We report a patient with Cat eye syndrome (CES) associated with anatomical asplenia. To the best of our knowledge, there have been no prior reports of this association. Screening for asplenia in CES is potentially important, as asplenia places patients at increased risk for life-threatening bacterial infections. Hence patients with CES without a spleen may require the same routine precautions as any other asplenic patients, with penicillin prophylaxis and immunizations to protect against encapsulated organisms such as Streptococcus pneumoniae, Haemophilus influenzae type b, and Neisseria meningitidis .